2016
DOI: 10.1242/jeb.128439
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of electrical excitability in fish hearts

Abstract: Environmental temperature has pervasive effects on the rate of life processes in ectothermic animals. Animal performance is affected by temperature, but there are finite thermal limits for vital body functions, including contraction of the heart. This Review discusses the electrical excitation that initiates and controls the rate and rhythm of fish cardiac contraction and is therefore a central factor in the temperature-dependent modulation of fish cardiac function. The control of cardiac electrical excitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 115 publications
(140 reference statements)
4
71
1
Order By: Relevance
“…Several seasonal differences were evident in transcript expression of K + channel subunits. A major change occurred in genes (kcnh2, kcnh6) coding for the rapid component of the delayed rectifier K + current, I Kr , the major repolarising current of the fish hearts (Vornanen, 2016). kcnh6 was strongly up-regulated in winter, consistent with earlier findings showing that I Kr is up-regulated under cold acclimation in practically all fish species that have been studied Hassinen et al, 2008a;Galli et al, 2009;Haverinen and Vornanen, 2009b;Abramochkin and Vornanen, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Several seasonal differences were evident in transcript expression of K + channel subunits. A major change occurred in genes (kcnh2, kcnh6) coding for the rapid component of the delayed rectifier K + current, I Kr , the major repolarising current of the fish hearts (Vornanen, 2016). kcnh6 was strongly up-regulated in winter, consistent with earlier findings showing that I Kr is up-regulated under cold acclimation in practically all fish species that have been studied Hassinen et al, 2008a;Galli et al, 2009;Haverinen and Vornanen, 2009b;Abramochkin and Vornanen, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…The physiological basis of cardiac arrhythmias is being explored (Badr et al, 2016;Vornanen, 2016), but more important to present concerns, they are observed with acute warming of perfused working heart preparations (A. Badr and M. Vornanen, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, acute warming may lead to cardiac arrhythmia or cardiac collapse (Anttila et al ., ; Eliason et al ., ; Farrell et al ., ; Verhille et al ., ; Vornanen et al ., ). With temperature acclimation, many fishes, but not all, can reset f H and hence their cardiac response to acute warming (Drost et al ., ; Ferreira et al ., ; Klaiman et al ., ; Vornanen, ). For example, cold‐acclimation of cold‐active fish like the rainbow trout Oncorhynchus mykiss (Walbaum 1792) results in a compensatory elevation in f H , which helps maintain heart and whole organismal activity despite the direct effects of being colder (Aho & Vornanen, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The sarcoplasmic reticulum Ca 2+ ‐ATPase (SERCA) pump then restores SR calcium (Monfredi et al . ; Vornanen, ). In contrast, the membrane clock mechanism involves a funny current ( I f ) via an inward hyperpolarisation‐activated mixed Na + and K + channel (HCN), which produces a spontaneous depolarisation of the pacemaker cell that triggers an action potential (Brown et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation